METAFORA DALAM KUMPULAN CERPEN CHUBB CHATTĀ ATHRĀFI ‘L-ASHĀBI’ KARYA AHCMAD AL-GHARBĀWĪ - Jawat Nur, Abdul (Arabic Letters and Department, 2014)
This paper is aimed to disscuss metaphor in theÂ anthology of short stories Chubb ChattÄAthrÄfi â€žl-AshÄbiâ€Ÿ written by Ahcmad Al-GharbÄwÄ« (2010). The short stories anthologyhas studied because there are metaphores utterance used in. Three metodes are used inthis research, that are the metod of collecting data, analyzing data, and reporting dataanalyzing. Depends on the study of metaphor in this short stories anthology, there arefour metaphor used, namely anthropomorphic metaphor, animal metaphor, from concretto abstract metaphor, and synesthetic metaphor. The function of metaphors in thatanthology is expressive function from the writter to arise the puitical and interestical style in his work,Â so it makes the readers not to be boring to follow the story.